2018
DOI: 10.1016/j.dib.2018.04.142
|View full text |Cite
|
Sign up to set email alerts
|

The effect of non traditional teaching methods in entrepreneurship education on students entrepreneurial interest and business startups: A data article

Abstract: Traditional methods of teaching entrepreneurship in universities involves more theoretical approaches which are less effective in motivating considerations for an entrepreneurship career. This owes to the fact that such techniques essentially make students develop a dormant attitude rather than active participation. Expert views suggest that experiential entrepreneurship teaching methods in universities which involve practical activities and active participation can be considered salient to students’ developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 0 publications
2
33
0
10
Order By: Relevance
“…The previous teaching methods need to be checked with the current students' exposure to technology. This is because, traditional method used to teach entrepreneurship in the context of higher learning institutions was a major constraint in developing students with entrepreneurship mindset (Olokundun et al, 2018). This is in line with the statement by Olokundun et al (2018) that found practical use of real-life experience into best practices in entrepreneurial teaching and learning at universities.…”
Section: Teaching and Learning Methodssupporting
confidence: 60%
“…The previous teaching methods need to be checked with the current students' exposure to technology. This is because, traditional method used to teach entrepreneurship in the context of higher learning institutions was a major constraint in developing students with entrepreneurship mindset (Olokundun et al, 2018). This is in line with the statement by Olokundun et al (2018) that found practical use of real-life experience into best practices in entrepreneurial teaching and learning at universities.…”
Section: Teaching and Learning Methodssupporting
confidence: 60%
“…The health education methods of publicity materials and bulletin boards tended to let migrant workers learn by themselves. This traditional way of education might be annoying, making it difficult to stimulate an interest of learning [37,38]. Online education also requires self-study but played a significant role in improving the healthcare-seeking behavior of migrant workers.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, for future research, it would be convenient to follow up on the present investigation; likewise, to involve other variables that could help to understand the emerging concept of the entrepreneurial university in the Mexican context within the technology and engineering field. Thus, the relevance of the traditional teaching method should be thoroughly reviewed in order to improve university entrepreneurial education [69][70][71][72].…”
Section: Resultsmentioning
confidence: 99%